2021
DOI: 10.1177/1759720x211033679
|View full text |Cite
|
Sign up to set email alerts
|

Switching from originator adalimumab to biosimilar SB5 in a rheumatology cohort: persistence on treatment, predictors of drug interruption and safety analysis

Abstract: Aims: Medical and non-medical switching strategies have been adopted in Europe in the last few years. We aimed to investigate persistence on treatment with a SB5 Adalimumab (SB5) biosimilar after switching from Adalimumab (ADA) originator among patients with inflammatory rheumatic musculoskeletal diseases (iRMD), identifying possible predictors of drug interruption and describing adverse events. Method: iRMD patients previously switched to SB5 after at least 6 months of ADA were enrolled. Data on concomitant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Similarly, Bruni C et al [14] reported no difference in the control of disease activity, everyday life disability, and safety after switching from the adalimumab originator to SB5 in patients with PsA. Another recent study carried out by the same researchers [15] on a population of 172 patients (59 with PsA) showed that patients who had switched from the adalimumab originator to SB5 maintained a satisfactory level of persistence in treatment. Among patients who switched back to the originator, there were 3 patients with PsA who achieved disease control once switched back.…”
Section: Main Outcomes Main Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, Bruni C et al [14] reported no difference in the control of disease activity, everyday life disability, and safety after switching from the adalimumab originator to SB5 in patients with PsA. Another recent study carried out by the same researchers [15] on a population of 172 patients (59 with PsA) showed that patients who had switched from the adalimumab originator to SB5 maintained a satisfactory level of persistence in treatment. Among patients who switched back to the originator, there were 3 patients with PsA who achieved disease control once switched back.…”
Section: Main Outcomes Main Resultsmentioning
confidence: 94%
“…Fourteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25]49] evaluated the effects in terms of the efficacy and safety derived from the switch among adalimumab products. All studies were carried out in Europe (10/14 in Italy).…”
Section: Adalimumab Switching Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies were conducted in patients with rheumatologic diseases such as RA, AS, and PsA, who were treated with SB5 [ 21 23 ].…”
Section: Real-world Evidencementioning
confidence: 99%
“…Two observational studies investigated switching from ADL to SB5 [ 21 , 22 ]. The first (Bruni et al [ 21 ]), which focused on safety, enrolled 172 patients with inflammatory arthritis, including 34 patients with RA, 59 patients with PsA, and 61 patients with AS. All enrolled patients previously had received at least 6 months of treatment with ADL before switching to SB5.…”
Section: Real-world Evidencementioning
confidence: 99%